Samotność spojrzenia. O czułej pracy dokumentalisty - Michałowska, Marianna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
In a cultural discourse a solitude is often presented as a state of mind or a social situation. In the both cases, to be lonely means to be alienated, lost or generally unhappy. Is it possible, however, to look at the solitude differently and to notice its potential power of phenomenological insight into the world? In the article the solitude leads the artist to the self reflection and creation. Having based on chosen examples of photography by Zbigniew Tomaszczuk I discuss the idea of contemplation of the world that is possible only when the photographer looks through the lens of the camera from a sole distance. I consider three aspects of such gaze like: 1. a looking at the landscape, which distances the spectator from the time and space and helps in the composition of the frame, 2. a looking at the own past from the distance of passing time, and finally 3. narrating the home city through a visual metaphor